2011
DOI: 10.1159/000327352
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmunoendocrine Interactions in Patients with Recurrent Major Depression, Increased Early Life Stress and Long-Standing Posttraumatic Stress Disorder Symptoms

Abstract: Background: Traumatic events experienced in childhood may lead to psychiatric diseases in adult life, including major depressive disorder (MDD). It remains obscure to what extent early life stress (ELS) is associated with biologically relevant changes in MDD. Objective: We investigated both neuroendocrine and immunological correlates in recurrent MDD with ELS and current posttraumatic stress disorder symptoms. Methods: Thirty-eight female MDD patients with or without childhood trauma and 15 healthy controls to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 134 publications
0
18
0
3
Order By: Relevance
“…Indeed, elevated levels of IL‐1β, IL‐12, and TNF‐α were observed in CM subjects in this study. Furthermore, increased inflammatory markers have been previously reported in individuals with exposures of early child abuse . Given that, it is possible that increased IL‐1β, IL‐12, and TNF‐α levels may be the result of early life adversity in subjects undergoing CM.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, elevated levels of IL‐1β, IL‐12, and TNF‐α were observed in CM subjects in this study. Furthermore, increased inflammatory markers have been previously reported in individuals with exposures of early child abuse . Given that, it is possible that increased IL‐1β, IL‐12, and TNF‐α levels may be the result of early life adversity in subjects undergoing CM.…”
Section: Discussionmentioning
confidence: 99%
“…Hart and Rubia (), for instance, suggested that some of the limitations of studies of the association between maltreatment and cognition could be due to the inclusion of participants with psychiatric disorders, making it difficult to differentiate between the cognitive impact of the abuse itself, of the psychiatric condition, and of the interaction between these factors. The most common psychiatric illnesses diagnosed in victims of childhood maltreatment are PTSD (Borges & Dell'Aglio, ; De Bellis, Hooper, Woolley, & Shenk ; De Bellis et al., ; Thomas & De Bellis, ; Woon & Hedges, ), depression (Brietzke et al., ; Danielson, de Arellano, Kilpatrick, Saunders, & Resnick ; Kendler, Kuhn, & Prescott ; Lopes et al., ), and bipolar disorder (Brietzke et al., ; Daruy‐Filho, Brietzke, Lafer, & Grassi‐Oliveira ).…”
Section: Discussionmentioning
confidence: 99%
“…A short-term, stress-induced increase in IFN-γ, macrophage inflammatory protein-3α, TNF-α, MCP-1, IL-1α, IL-1β and IL-6 can enhance the immunization phase of cell-mediated immunity (75,76). Nevertheless, chronic stress can lead to a reduction in the number of cytokines, including IFN-γ, IL-2 and IL-12, due to the inhibitory effect of GC, NE and E, which have an important antitumor function (77,78). Chronic stress-induced neuroendocrine changes have been found to suppress the immune response, including NK cell cytotoxicity, phagocytosis, inflammatory cytokine production and cytotoxic T-cell activity, compromising the most important effectors of the immune response against tumors (66).…”
Section: Mechanisms Underlying the Effects Of Stress On Tumorigenesismentioning
confidence: 99%